(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Marketing strategies and channel adopted by life insurance companies plays an important role in luring the target segment. As insurance in as an intangible product therefore to differentiate the product and afterwards to make consumer understand the USP of their product is a challenging task, only strong relationships with customers and word of mouth publicity help them to compete successfully. Companies require a strong focus on the basics of effective marketing, with the changing needs and awareness of consumer, companies required to address consumer in all possible new ways of technological advancement along with existing distribution channel As far as case of LIC is concern still it dominate the market with approx 70 percent market share but facing stiff competition from private players in the market